(untitled) (Argos, 2025)
The pleasures of wine and love were the main topics that decorated the vases of the banquets. Guests were entertained by beautiful women or ephebi who played music, performed acrobatics and offered their naked bodies. By "reading" the painted images, we can become witnesses to the passion and the intemperance of those participating in the symposium. The vases were also used for drinking, pouring wine mixed with water, to stimulate the senses, exalt passions and temper the inhibitions.